The last midwife [large type] - Dallas, Sandra (Center Point Large Print, 2015)
It is 1880 and Gracy Brookens is the only midwife in a small Colorado mining town where she has delivered hundreds, maybe thousands, of babies in her lifetime. She is a gifted and important resource for the women of her hardscrabble community, a position earned through wisdom and trust. Most women in Swandyke couldn't even imagine getting through their pregnancy and labor without Gracy by their sides. But everything changes when a baby is found dead--and the evidence points to Gracy as the killer. Gracy knows she didn't commit the crime. But her innocence isn't quite that simple, either. She knows things and that's dangerous. Invited into her neighbors' homes during their most intimate times, she can't help what she sees or hears. A woman sometimes says things in the birthing bed, when life and death seem suspended within the same moment. Gracy has always tucked those revelations away, even the confessions that have cast shadows on her heart. With her friends taking sides and a trial looming, Gracy must decide whether it's worth risking everything to prove her innocence.